2014
DOI: 10.1055/s-0040-1703763
|View full text |Cite
|
Sign up to set email alerts
|

Implant Abutment Connection: Biomechanical Perspectives

Abstract: Abstract:Dental implant therapy is a fast growing and brightest prospect in the rehabilitation of completely and partially edentulous arches. Study of implants has become indispensable and so is the biomechanics related to dental implant therapy. Implant abutment connection is a crucial synapse between the implant and the abutment. It is an important determinant of the strength and stability of an implant supported restoration, and play a major role in the success of the implant. The review describes the biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…As such, the abutment head should also be flat on top to increase the clamping force in the screw head and the tensile force in the threads. [ 36 ]…”
Section: Anagementmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the abutment head should also be flat on top to increase the clamping force in the screw head and the tensile force in the threads. [ 36 ]…”
Section: Anagementmentioning
confidence: 99%
“…A higher torque magnitude can be used on the titanium alloy abutment screw and female component (implant body). [ 36 ] Titanium retaining screws are stronger than gold, but have a lower modulus of elasticity; metal fatigue will produce a gold screw fracture before the titanium retaining screw is affected. [ 37 ] The major disadvantage of titanium retaining screws is their tendency to cause galling, which results in excessive friction between the two mating surfaces there by causinga localized welding with a further roughening of the mating surfaces.…”
Section: Anagementmentioning
confidence: 99%
“…Different abutment screw designs were tested in the present study. Previous studies have evaluated the ability of tapered head and flat head screws to maintain preload, 29,30 reporting that flat head screws were preferable for preload maintenance because of even force distribution within the screw and the head of the screw. It was also reported that longer stems provide favorable elongation during preload development.…”
Section: Discussionmentioning
confidence: 99%
“…The early invented external hexagon connection resulted in great possibility of screw loosening problems due to high incidence of rotational misfit giving rise to improper microbial seal. (26,29,30) The shift towards the commonly used nowadays internal connection designs with alteration of the connection part inside the implant body and at a lower level to the implant coronal portion has given this design its unique advantage. (31,32) The internal implantabutment design resulted in better occlusal forces distribution and improved abutment stability in consequence of lowering of the rotational centre and protection of the retention screws, thus, resisting excessive lateral forces.…”
Section: Discussionmentioning
confidence: 99%